Common Sampling Errors in Research Studies. - Spolarich, Ann E. (Journal of Dental Hygiene, 2023)
Proper sample selection is based on the study purpose, research question(s), and study design. Investigators must use care to select a sample population that is representative of the source and target populations. Welldefined inclusion and exclusion criteria serve as guidance when screening potential candidates for eligibility for participation in a study. Sampling and non-sampling errors may influence study outcomes and generalizability of results. The purpose of this short report is to review common sampling errors made when designing a study and when reporting study outcomes.